Hand-Based Biometric Recognition Technique - Survey - Příhodová, Kateřina; Hub, Miloslav (My University, 2020)
In today's modern world, reliable automatic personal recognition is a crucial area of discussion, primarily because of the increased security risks. A large number of systems first require the recognition of a person before they can access their services. Biometric recognition can be used, which can be understood as automatic identification or automatic verification of persons based on physiological or behavioural characteristics. Examples of biometric characteristics may be the fingerprint, face, signature, hand geometry. There are many approaches, and each has its pros and cons. However, there is currently no current extensive research and evaluation of hand-based biometric systems. Given the user-friendliness of these systems and the needs of society, this article aims to compare different methods of biometric recognition based on hand, so that the article reduces the entry barrier into this area of research. Furthermore, the article aims to determine the research gap and suggest possible directions for research in the future.
Metody rozpoznávání osob na bázi ruky - Průzkum
Keywords: hand geometry; biometric recognition; hand-base authentication; geometrie ruky; biometrické rozpoznávání; autentizace na bázi ruky